2004
DOI: 10.1097/00001756-200410050-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GM-CSF on the neural progenitor cells

Abstract: Granulocyte macrophage colony stimulating factor (GM-CSF) is a potent hematopoietic cytokine, which stimulates stem cell proliferation in the bone marrow. We now report that GM-CSF receptors expressed on neural progenitor cells and can mediate a biological response in cells to treat with GM-CSF treated neural progenitor cells exhibited a proliferative response and a marked decrease in terminal differentiation to mature neuron or astrocytes. GM-CSF treatment also suppressed neural progenitor cell apoptosis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 14 publications
2
38
0
Order By: Relevance
“…GM-CSF appears to be locally produced and acts either direct on RGCs or via regulating the function of microglial cells, which are of hematopoietic origin and resemble intraneural resident dendritic cells [54,55]. GM-CSF can cross the blood-brain and blood-cerebrospinal-fluid barriers, and may act as an inflammatory cytokine with neuroprotective effects [49,[56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…GM-CSF appears to be locally produced and acts either direct on RGCs or via regulating the function of microglial cells, which are of hematopoietic origin and resemble intraneural resident dendritic cells [54,55]. GM-CSF can cross the blood-brain and blood-cerebrospinal-fluid barriers, and may act as an inflammatory cytokine with neuroprotective effects [49,[56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…The main functions of GM-CSF are to stimulate proliferation and differentiation of bone marrow stem cells, and inhibit apoptosis of hematopoietic cells [1]. However, it is also well known that the GM-CSF receptor is expressed on many neural cells types in the developing brain and in the mature central nervous system (CNS), and GM-CSF has neurotrophic and neurogenic activities [2][3][4][5][6]. Our group and others have demonstrated that GM-CSF have neuroprotective effects on cultured neuronal cells in vitro and in animal models of CNS injuries such as spinal cord injury (SCI), brain ischemic injury and Parkinson's disease [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…GM-CSF can function as a neurotrophic factor [9] and induce proliferation of neural progenitor cells (NPCs) [10] in vitro. Therapeutic effect of GM-CSF is already well known in the peripheral nervous system (PNS) injury by activating macrophages and Schwann cells to remove myelin debris [11][12][13].…”
Section: Introductionmentioning
confidence: 99%